2004
DOI: 10.1109/ted.2004.835996
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Endurance of NOR Flash EEPROM Cells Under CHISEL Programming Operation—Impact of Technological Parameters and Scaling

Abstract: Abstract-The impact of technological parameter (channel doping, source/drain junction depth) variation and channel length scaling on the reliability of NOR Flash EEPROM cells under channel initiated secondary electron (CHISEL) programming is studied. The best technology for CHISEL operation has been identified by using a number of performance metrics (cycling endurance of program/erase time, program/disturb margin) and scaling studies were done on this technology. It is explicitly shown that from a reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Measurements were performed on isolated, fully scaled bitcells having finished of 0.3 through 0.2 m, width (W) of 0.3 m, tunnel oxide and ONO interpoly dielectric (IPD) thickness of 12 and 20 nm, respectively and gate coupling of about 0.55. The devices used in this paper are of HL type [17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements were performed on isolated, fully scaled bitcells having finished of 0.3 through 0.2 m, width (W) of 0.3 m, tunnel oxide and ONO interpoly dielectric (IPD) thickness of 12 and 20 nm, respectively and gate coupling of about 0.55. The devices used in this paper are of HL type [17].…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that drain disturb after P/E cycling increases for the charge gain mode (from erased cells) and decreases for the charge loss mode (from programmed cells), for cycling under a wide range of drain and control-gate biases [15], [16]. Furthermore, the impact of technological parameters on drain disturb (both before and after cycling) has also been extensively studied [17]. However, to the best of our knowledge, the mechanism behind the impact of P/E cycling on drain disturb has not been convincingly explained so far [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies demonstrated the important role of lattice heat and thermal activation of the lo w voltage impact ionization in deep-submicro meter M OSFETs [132]. In addition, the recent studies of silicon on insulator (SOI) devices by the classical HDM , showed certain anomalies due to lack of a heat evacuation mechanism at the insulator interface [133].…”
Section: Lattice Heat Conservation Equationmentioning
confidence: 99%
“…Compared with CHE, CHISEL offers faster program speed under equivalent power, lower power consumption under similar speed, better cycling endurance of V TH window, and lower degradation of program time T P [6], [9], [10], [16], [17]. CHISEL also leads to a selfconvergent programming, giving a better control over program V TH [4], [6], [11].…”
mentioning
confidence: 99%